UTeM Engineering students’ intention to participate in on-campus entrepreneurial activities / Najihah Md Akhir - Md Akhir, Najihah (Faculty of Business and Management, 2018)
The issue is the participation of students in on-campus entrepreneurial activities is low than expected. So, the main purpose of this study is to explore the factors that influence students’ intention to participate in on-campus entrepreneurial activities. Moreover, the research objectives are to determine the correlation between attitude toward entrepreneurship and perceived feasibility with UTeM engineering students’ intention to participate in on-campus entrepreneurial activities, to investigate whether attitude toward entrepreneurship and perceived feasibility influence the UTeM engineering students’ intention to participate in on-campus entrepreneurial activities. The methodology is to achieve the above objectives, correlation coefficient analysis was used to achieve the first objective while multiple regression analysis was used to test the hypotheses which are the first looked into the influence of attitude towards entrepreneurship on students’ intention to participate in on-campus entrepreneurial activities, and the second focused on the influence of perceived feasibility on students’ intention to participate in on-campus entrepreneurial activities. A questionnaire was used and participants were drawn from 265 engineering students from UTeM. This study used SPSS version 2.0 to analyze the data. The outcome of the study indicated the patterns which are attitude towards entrepreneurship and perceived feasibility are positively associated with students’ intention to participate in on-campus entrepreneurial activities. Value of the research findings suggest that both attitude towards entrepreneurship and perceived feasibility are important factors influencing students’ intention to participate in on-campus entrepreneurial activities. This paper aims to identify some important steps to increase the students’ involvement. Thus, this study should prove to be of great value to those in university entrepreneurship. The keywords are attitude towards entrepreneurship and perceived feasibility. This paper type is research paper.